Corporate Beneficial Ownership Transparency Legal Frameworks: A Comparative Regulatory Analysis Indonesia & Philippines - William Sepvano The (Siyasah Dusturiyah: State Law Review, 2026)
This article examines the legal dualism within Indonesia's beneficial ownership transparency framework, which explicitly contradicts the Investment Law and heavily limits compliance. Employing a doctrinal method through a strong comparative approach, this study critically contrasts Indonesia's passive declarative regime against the progressive investigative-digital framework of the Philippines under SEC MC 15/2025. Primary findings indicate that while Indonesia still relies on a loose twenty-five percent threshold without extraterritorial reach, the Philippines has actively mandated a precise twenty percent threshold, nine deterministic ownership categories, and the cross-border digital registry HARBOR. Consequently, Indonesia's current regulatory framework suffers from normative stagnation and severely lacks independent verification mechanisms. To eliminate information asymmetry and comply with international standards of the Financial Action Task Force, Indonesia urgently needs to enact a standalone Corporate Transparency Act. This crucial legal reform must integrate a multi-layered control taxonomy and establish a cross-verified database to fully protect the national corporate ecosystem.